Alteration of BDNF and noradrenergic markers in locus coeruleus in a mouse model of cancer-induced bone pain - Man Yuan; Long Zhang; Haili Zhu; Min Xie (PLoS ONE, 2025)
The locus coeruleus (LC) is the principal source of noradrenaline (NA) in the central nervous system. In neuropathic pain states, nociceptive stimuli activate LC. This study examined the expression and localization of BDNF and NE neuron-specific proteins in the LC of mice with cancer-induced bone pain (CIBP). Behavioral experiments demonstrated that CIBP mice exhibited persistent spontaneous pain, mechanical and thermal hyperalgesia, and deficits in locomotor activity and motor coordination. H&E and TRAP staining revealed trabecular bone destruction and increased in osteoclast activity. Immunostaining showed elevated expression of neuronal activity marker c-Fos in the LC. Additionally, upregulation of noradrenergic markers - tyrosine hydroxylase (TH) and dopamine β-hydroxylase (DBH) – as well as brain-derived neurotrophic factor (BDNF), was observed in the LC. In vitro studies indicated that inhibition of the BDNF/TrkB signalling pathway reduced the expression of noradrenergic markers. Anterograde tracing, achieved by Fluoro-ruby injection into the LC and subsequent detection of Fluoro-ruby colocalised with TH and DBH in spinal cord, confirmed LC-spinal cord projections. Immunofluorescence analysis demonstrated increased fluorescence intensities of TH, DBH, c-Fos, phosphorylated cAMP-response element- binding protein (pCREB), and α2A receptor in the spinal cord, alongside reduced intensities of enkephalin (ENK) and GABA A Receptor β2 (GABRB2). Western blotting further corroborated elevated expression levels of TH and c-Fos in spinal cord tissue. In summary, CIBP mice exhibited enhanced neuronal activity in the LC, upregulation of noradrenergic markers, and BDNF/TrkB-mediated modulation of noradrenergic neurons. Concurrently, inhibitory signalling was attenuated in the SDH.